Trends in non-destructive testing of rock bolts - Mario Bačić; Kenneth Gavin; Meho Saša Kovačević (Građevinar, 2019)
Rock bolts represent a critical element for many rock mass stabilization, tunnel construction, and underground work projects. Therefore, the evaluation of their condition is vital for proving their functionality over the entire life-cycle of structures. A number of techniques for quantifying condition of rock bolts are presently applied or are being developed. These include acoustic-based and vibration-based methods, which take advantage of various types of sensors and signal-processing tools. This paper provides an overview of available non-destructive test methods for rock bolts, considering both current practice and state of the art approaches.